1973
DOI: 10.1163/156853973x00120
|View full text |Cite
|
Sign up to set email alerts
|

Snake Avoidance in Feral and Laboratory Reared Squirrel Monkeys

Abstract: The latency of food retrieval and other behaviours in the presence of a live boa constrictor and other snake-like stimuli was observed in three groups of squirrel monkeys (adult feral, adult laboratory reared, and immature laboratory reared). The principal results were as follows: 1. Both of the laboratory reared groups retrieved food within about five or fewer sec in the presence of any stimulus, including the live snake. 2. The retrieval latencies of the adult feral group were longest in the presence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 9 publications
0
17
1
Order By: Relevance
“…This widely generalized response across a wide variety of test stimuli contrasts with fmdings in prior experiments (Murray & King, 1973;King & Huber, Note 1) showing a sharp discrimination by squirrel and capuchin monkeys between snakes and snake models as measured by food retrieval latencies in the presence of those stimuli. The shape of the stimuli was an important variable in these studies.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This widely generalized response across a wide variety of test stimuli contrasts with fmdings in prior experiments (Murray & King, 1973;King & Huber, Note 1) showing a sharp discrimination by squirrel and capuchin monkeys between snakes and snake models as measured by food retrieval latencies in the presence of those stimuli. The shape of the stimuli was an important variable in these studies.…”
Section: Discussioncontrasting
confidence: 64%
“…Behaviors of the monkeys were tested in the presence of the following five stimuli, which were identical to those previously used by Murray and King (1973) and by King and Huber (Note 1) in their studies of snake avoidance in squirrel monkeys and capuchin monkeys, respectively: (1) a live boa constrictor (Boa constrictor constrictor), approximately 61 cm long (because of the relatively low temperature of the test room, the snake evidenced virtually no movement during the test periods); (2) a coiled rubber snake, 61 cm long, painted to resemble the live snake's pattern of coloration; (3) a coiled rubber snake, 61 cm long, painted a uniform gray; (4) a gray coiled rubber tube, 61 cm long, painted with red spots; (5) a wooden block, 3.8 x 3.8 x 5 em, painted gray.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The plausibility of this explanation was supported by Stephenson's (1967) experiment, which demonstrated that rhesus monkeys could learn by observation to fear relatively arbitrary objects. In a study similar to that of Joslin et al (1964), Murray and King (1973) showed that there were systematic differences in wild- …”
mentioning
confidence: 86%
“…The plausibility of this explanation was supported by Stephenson's (1967) experiment, which demonstrated that rhesus monkeys could learn by observation to fear relatively arbitrary objects. In a study similar to that of Joslin et al (1964), Murray and King (1973) showed that there were systematic differences in wildCopyright 1981 Psychonomic Society, Inc.and lab-reared squirrel monkeys' fear of snakes. Wildreared, but not lab-reared, squirrel monkeys displayed significantly longer food-reach latencies when presented with a live snake or a snake-like object than when presented with a neutral object.…”
mentioning
confidence: 91%